ENHANCING ADOLESCENT ROAD SAFETY THROUGH BEHAVIORAL THEORY AND DRIVING SIMULATION: PENINGKATAN KESELAMATAN BERLALU LINTAS REMAJA DENGAN PENDEKATAN TEORI PERILAKU DAN SIMULASI MENGEMUDI - Leinia, Audinda Virsa; Asid, Nurul Jannah; Amini, Iqlima Nuril; Dlauissama; Rachma, Siti Talitha; Putra, Alwan Gangsar Brillian; Loekito, Irfan Prasetyo; Arthaningtyas, Desy Ratna (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Indonesia experiences extremely high traffic accident rates, with motorcyclists and young drivers disproportionately affected due to prevalent human factors, insufficient safety education, and peer-influenced risky behaviors. Objective: In response, this community service initiative integrates comprehensive theoretical instruction with driving simulations to enhance road safety awareness and improve cognitive driving behaviors among adolescent students, specifically those at Sekolah Indonesia Kuala Lumpur. Method: This community service initiative employed a methodology that integrated theoretical instruction based on the Theory of Planned Behavior with virtual driving simulations, assessing its impact on adolescent drivers' road safety awareness through pre- and post-tests and participant satisfaction surveys. Results: The combined theoretical and simulation-based intervention was highly effective in enhancing adolescent drivers' perception of safety, as evidenced by a 32%, 32%, and 33% increase in their correct answer rates for Attitude, Subjective Norms, and Perceived Behavioral Control, respectively. Conclusion: The combined theoretical and simulation based intervention effectively improved road safety attitudes, subjective norms, and perceived behavioral control among young, inexperienced male high school drivers with a history of incidents, consequently promoting cognitive and attitudinal shifts toward safer road behavior.